The prevalence of alcohol and pre-workout caffeine consumption and their effect on injuries and sleep disorders in young elite soccer players - E. D. Koroleva; M. S. Butovskiy; G. I. Malyakin; A. M. Lazarev; D. V. Telyshev; T. M. Vakhidov (National Electronic Information Consortium (NEICON), 2023)
Aim: to study the prevalence of alcohol and pre-workout caffeine use and their impact on sleep quality and injury among the young soccer players.Methods: this study examined the prevalence of alcoholic beverages and pre-workout caffeine consumption in young soccer players, as well as the effect of these substances on sleep disorders and injuries among 236 elite athletes aged 11-21 years.Results: 16.5 % of soccer players use pre-workout caffeine. Most often 1-2 times per week. Caffeine consumption is weakly positively correlated with age (p < 0,001, R = 0,41.) and is most common in the age group of 19-21 years with consumption rates at 58.8 %. 17.3 % of young soccer players consume alcohol moderately and its consumption significantly correlates with age. Most often alcohol was consumed at the age of 19-21 years. Alcohol and caffeine consumption are significantly, but weakly correlated with the risk of severe sleep disorders on the Athlete Sleep Behavior Questionnaire (ASBQ). However, injuries during matches and training sessions did not depend on alcohol (p = 0.076) or caffeine (p = 0.14) consumption according to the Kraskal - Wallis test. At the same time, sleep disorders on the ASBQ significantly correlated with injury.Conclusion: the widespread use of alcohol and caffeine, and their negative impact on sleep among soccer players aged 11-21 years were revealed, but there was no connection between the use of these substances and injuries.